Employee's job security during economic downturn - Lucky, Esuh Ossai Igwe; Minai, Mohd Sobri; Hamzah, Abdul Rahman (Inderscience Publishers, 2013)
This concept paper proposes a conceptual model of employee's job security during economic downturn.Due to the turbulent global economy, natural resources are under strain, austerity cuts are threatening public sector jobs. Organisations are laying off their workforce in order to cope with the economic conditions. The future has become more unpredictable and uncertain about the workers keeping their jobs.The fear of losing their jobs in the midst of uncertainty becomes a great concern that needs an urgent attention.The question remains, should the organisations lay off their workforces? Or should the employees continue to holding on to their jobs in the midst of this economic turbulence? Based on this, the paper examined theoretical issue relating to employees job security in relation to economic downturn.It presents a conceptual model to examine employees' job security during economic downturns, and further argued on the possibilities of employees holding on to their jobs during economic turbulence.